MODEL PENGENDALIAN PERSEDIAAN BAHAN BAKU KEDELAI TERHADAP PROSES PRODUKSI TAHU TEMPE PADA UD. RESTU PASUI KECAMATAN BUNTU BATU KABUPATEN ENREKANG - Misra Misra; Abdul Muttalib; nurinayah nurinayah (Universitas Muhammadiyah Makassar, 2019)
This study aims to determine the control of inventory of raw materials for soybeans on the production process of tempe tofu at UD. Restu Pasui, Buntu Batu District, Enrekang District. This type of research is a case study so that the leadership of UD. Restu is used as a source to obtain information according to research needs. The data is then processed using a quantitative descriptive approach and Analysis of the Economic Production Quantity (EPQ). with the results of ordering raw materials obtained which is 62.42. Based on these results it can be seen that UD. He agreed by increasing the amount of tempe production so that raw materials in the warehouse did not accumulate so that they could fulfill the consumers' desires. Whereas for order results calculated using Order Quantity Analysis (EOQ) per month amounting to 13.75 or 14. Based on the above results it can be concluded that soybean raw material supplies at UD. Restu is already economical.